Ecological and biological features of Gentiana septemfida in the south of Western Siberia - Prokopyev, Alexey S.; Kataeva, Tatjana N.; Yamburov, Mikhail S. (Acta Biologica Sibirica, 2024)
Gentiana septemfida Pall. is a montane species native to the Caucasus, Asia Minor, and Western Siberia. This protected plant species from the Siberian flora has significant medicinal and ornamental value. Field studies were conducted in the forest zone of the West Siberian Plain (Tomsk Region) and in the Altai highlands (Seminsky, Kuraisky and North Chuysky ridges of the Republic of Altai). It was found that the distribution of G. septemfida in the southern part of Western Siberia is closely associated with meadow cenoses. In the Altai Mountains, this species occurs near the upper boundary of the forest belt, in forest meadows, open glades, and bushy tundra with alpine and subalpine forbs. In the flat landscape, it is rarely encountered in river valleys among mesophilic tall grass meadows. The studied coenopopulations of G. septemfida are characterized as normal type, incomplete, ripening or mature. By morphological features were showed that coenopopulations from Seminsky Ridge and Tomsk Region have the most optimal conditions for plant growth and development. In nature, G. septemfida reproduces by seeds. However, in some areas seed productivity significantly reduced due to annual damage of fruits by insect pests. The lowest level of the reproductive potential was in Seminsky Ridge coenopopulation. The assessment of plant introduction in the southern part of the Tomsk Region classified G. septemfida as a stable plant. The gene pool established in the Siberian Botanical Garden, Tomsk State University, plays a crucial role in successful conservation of the species in ex situ conditions.